Empowerment of the mothers of children in a pediatric intensive care unit - Azevedo,Monique de Sales Norte (2018)
ABSTRACT Objective: to analyze the process of empowerment of the mothers of children hospitalized in a pediatric intensive care unit (PICU) according to Cheryl H. Gibson’s framework. Method: a qualitative study with a non-directive interview in groups was carried out with 14 mothers in the PICU of a pediatric teaching hospital in the state of Rio de Janeiro, whose data were submitted to thematic analysis. Results: all mothers underwent at least one phase of the process of empowerment. Some of them achieved the phase of participatory competence in the care for their children, being heard by the team and expressing their needs, opinions, and questions. Final considerations: attentive listening and information sharing with mothers is necessary, in order to provide essential support so that they undergo the process of empowerment, thus involving themselves in care and decision-making regarding their children.